Changes in Lipoprotein Lipase in the Heart Following Diabetes Onset. (January 2023) - Lee, Chae Syng; Zhai, Yajie; Rodrigues, Brian
Abstract: Due to its constant pumping and contraction, the heart requires a substantial amount of energy, with fatty acids (FAs) providing a major part of its adenosine triphosphate (ATP). However, the heart is incapable of making this substrate and attains its FAs from multiple sources, including the action of lipoprotein lipase (LPL). LPL is produced in cardiomyocytes and subsequently secreted to its heparan sulfate proteoglycan (HSPG) binding sites on the plasma membrane. To then move LPL to the endothelial cell (EC) lumen, glycosylphosphatidylinositol-anchored high-density lipoprotein-binding protein 1 (GPIHBP1) attaches to interstitial LPL and transfers it to the vascular lumen, where the LPL is ready to perform its function of breaking down circulating triglycerides (TG) into FAs. The endo-β-glucuronidase heparanase (Hpa) is unique in that it is the only known mammalian enzyme to cleave heparan sulfate (HS), thereby promoting the abovementioned release of LPL from the cardiomyocyte HSPG. In diabetes, it has been suggested that changes in how the heart generates energy are responsible for the development of diabetic cardiomyopathy (DCM). Following moderate diabetes, with the reduction in glucose utilization, the heart increases its LPL activity at the vascular lumen due to an increase in Hpa action. Although this adaptation might be beneficial to compensate for the underutilization of glucose by the heart, it is toxic over the long term, as harmful lipid metabolite accumulation, along with augmented FA oxidation and thus oxidative stress, leads to cell death. This coincides with the loss of a cardioprotective growth factor—namely, vascular endothelial growth factor B (VEGFB). This review discusses interconnections between Hpa, LPL, and VEGFB and their potential implications in DCM. Given that mechanism-based therapeutic care for DCM is unavailable, understanding the pathology of this cardiomyopathy, along with the contribution of LPL, will help us advance its clinical management.